1994
DOI: 10.1182/blood.v84.3.702.702
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of minimal disease in severe combined immunodeficient mice with disseminated Daudi lymphoma using chemotherapy and an immunotoxin cocktail

Abstract: Severe combined immunodeficient (SCID) mice injected intravenously with a human Burkitt's lymphoma cell line (Daudi) develop disseminated lymphoma (SCID/Daudi), which is fatal in 100% of the mice. Early treatment of these mice with either an immunotoxin (IT) cocktail (consisting of anti-CD19-ricin A chain plus anti-CD22-ricin A chain) or chemotherapy significantly prolonged survival but was not curative. Combination therapy with the IT cocktail and any one of three chemotherapeutic drugs (doxorubicin, cytoxan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Gemcitabine is the most successful form of chemotherapy for pancreatic cancer. Because CT have a mechanism of killing that is entirely different from the mechanism of kill of chemotherapy, many studies have shown that chemotherapy can be successfully combined with immunotoxin or cytotoxin therapy (41)(42)(43). Thus, the probability is high the effectiveness of DTEGF13 therapy can be heightened by combining it with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is the most successful form of chemotherapy for pancreatic cancer. Because CT have a mechanism of killing that is entirely different from the mechanism of kill of chemotherapy, many studies have shown that chemotherapy can be successfully combined with immunotoxin or cytotoxin therapy (41)(42)(43). Thus, the probability is high the effectiveness of DTEGF13 therapy can be heightened by combining it with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are really quite different, BU12 antibody having only a minimal therapeutic effect whether used alone or in combination with OKT10-SAPORIN. Moreover, in further studies it was shown that the anti-CD22 IT RFB4-dgA used in combination with the CD19 IT HD37-dgA in SCID-Daudi mice was only capable of prolonging survival and did not result in any cures unless used in conjunction with the small molecule cytotoxic drug doxorubicin, cytoxan or camptothecin (Ghetie et aL, 1994b). In contrast, we were able to produce an apparent 20% cure rate in SCID-Ramos mice treated with a combination of the two ITS BU12-SAPORIN and OKTlO-SAPORIN.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials with anti‐CD22 or other anti‐B cell immunotoxins have so far resulted only in partial and transient clinical remissions, probably due to the large tumour burden in treated patients ( Amlot et al , 1993 ; Sausville et al , 1995 ). However, Ghetie et al (1994 ) obtained eradication of minimal residual disease in SCID mice with Daudi lymphoma with a combination of chemotherapy and anti‐CD22 and anti‐CD19 ricin A chain immunotoxins. Therefore, it may be anticipated that the most promising clinical setting for the use of anti‐CD22 immunotoxins would be the treatment of minimal residual diseases, for instance after conventional chemotherapy or bone marrow transplantation, in patients with low‐grade B cell lymphoma or adult acute lymphoblastic leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The toxic moiety most commonly used in the preparation of anti‐CD22 immunotoxins has been the A‐chain of ricin ( Shen et al , 1988 ; Ghetie et al , 1988 , 1991, 1992, 1994; Van Horssen et al , 1996 ) and the efficacy of these compounds has been tested in several phase I–II clinical trials ( Vitetta et al , 1991 ; Amlot et al , 1993 ; Sausville et al , 1995 ). Immunotoxins can also be constructed with single‐chain ribosome‐inactivating proteins (type 1 RIP).…”
mentioning
confidence: 99%